Unsteady Mixed Convection Flow in the Stagnation Region of a Heated Vertical Plate Embedded in a Variable Porosity Medium with Thermal Dispersion Effects - Alharbi, S. M.; Hassanien, I. A. (IntechOpen, 2011)
None